The Impact of Time Management on Academic Procrastination among Doctoral Students in the Light of Psychological Empowerment as a Mediating Variable - ahlam tamri; mohammed Said djoual; Mokhtar rabhi (Journal of Excellence for Economics and Management Research, 2023)
This study aims to look into the role of psychological empowerment as a moderator in the relationship between time management and academic procrastination. The population of this study is made up of 301 doctoral students from Algerian Universities. The data was collected using an electronic questionnaire and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method in SmartPLS 4. The findings of this study confirm that time management affects academic procrastination, whereas psychological empowerment has no effect. Furthermore, the study discovered that psychological empowerment did not mediate the relationship between time management and academic procrastination. As a result, time management directly reduces academic procrastination among doctoral students rather than acting as a mediator through psychological empowerment